Dimensionering och utvärdering av elektrisk drivlina för regionalflyg med kapacitet för 30 passagerare - Design and evaluation of an electric propulsion system for regional aircraft with a capacity of 30 passengers - Leijon, William; Larsson, Anton; Svalander, Moses; Björkman, Rikard; Tang, Kenny; Gullberg, Albin (My University, 2025)
Abstract This bachelor’s thesis aims to design an electric propulsion system for a regional aircraft with a capacity of 30 passengers, specifically adapted for the Gothenburg– Stockholm route (approximately 400 km). The study investigates the feasibility of such electrification based on current technological limitations, with particular focus on battery technology energy density, the aircraft’s power requirements for the propulsion system, and the requirement for a 45-minute holding phase according to European aviation regulations. The project also includes societal and ethical aspects of the propulsion system, discussing the aircraft’s impact on the environment and society. The method is based on a simulation model developed in Python, where the flight is divided into different phases: start, takeoff, climb, cruise, descent, and a holding phase. The simulation relies on physical modeling to continuously calculate force and power requirements throughout the flight. Design parameters for the aircraft are taken from existing aircraft models such as the ES-30 and ATR 42-600, and are supplemented with assumptions. In addition, propeller efficiency has been modeled using an iterative solver that optimizes the propeller’s operating point based on experimental data. Literature studies have also been conducted to identify and compare technically suitable components, such as batteries and electric motors. The simulation shows that an electric propulsion system for the given route requires approximately 4 028 kWh of energy, which entails a battery mass requirement of 18 tons and an energy density requirement of 0.249 kWh/kg. The most powerdemanding phase is takeoff, where thrust of up to 68 kN is used. The battery accounts for a significant portion of the aircraft’s allowable takeoff weight, creating a practical limitation for full electrification. Even the most advanced batteries today do not offer a sustainable solution. The conclusion of the study is that while an electric propulsion system for the studied aircraft and route is technically possible, it is not practically viable to implement, as it would require an unrealistically large amount of batteries. A decisive factor is the requirement for reserve power. If this requirement was lower, electrification of the aviation industry would be more feasible. Sammanfattning Detta kandidatarbete syftar till att dimensionera en elektrisk drivlina för ett regionalflygplan med kapacitet för 30 passagerare, specifikt anpassat för sträckan Göteborg-Stockholm (ca 400 km). Arbetet undersöker genomförbarheten för en sådan elektrifiering med utgångspunkt i dagens tekniska begränsningar, med särskilt fokus på batteriteknologiernas energitäthet, flygplanets effektkrav på framdrivningssystemet och kravet på 45 minuter lång cirkulationsfas enligt europeiska luftfartsregler. Arbetet inkluderar även drivlinans samhälleliga och etiska aspekter där flygplanets påverkan på miljö och samhälle diskuteras. Metoden baseras på en simuleringsmodell framtagen i Python, där flygningen delas in i olika faser: takeoff, stigning, marsch, nedstigning samt en cirkulerande väntfas. Simuleringen baseras på en fysikalisk modellering för att löpande beräkna kraft- och effektbehov under flygningen. Parametrar för flygplanets utformning har hämtats från befintliga flygplansmodeller såsom ES-30 och ATR 42-600, och kompletteras med antaganden. Dessutom har propellerverkningsgrad modellerats med hjälp av en iterativ lösare, som optimerar arbetspunkten för propellern baserat på experimentell data. Utöver detta har även litteraturstudier genomförts för att identifiera och jämföra tekniskt lämpliga komponenter, som batterier och elmotorer. Simuleringen visar att en elektrisk drivlina för den aktuella sträckan kräver cirka 4 028 kWh energi, vilket medför ett krav på en batterimassa på 18 ton och energitäthetskrav på 0.249 kWh/kg. Den mest effektkrävande fasen är takeoff, där en total dragkraft på upp till 68 kN används. Batteriet motsvarar en betydande del av flygplanets tillåtna startmassa och skapar en praktisk begränsning för full elektrifiering. Även de mest avancerade batterierna idag tillhandahåller inte en hållbar lösning. Arbetets slutsats är att en elektrisk drivlina för det studerade planet på vald sträcka är tekniskt möjlig men inte praktiskt relevant att genomföra då det skulle kräva väldigt stora mängder batterier och detta är inte realistiskt att bygga. En avgörande faktor är kraven på reservkraft. Hade det varit lägre krav på reservkraft hade elektrifiering av flygindustrin varit mer realiserbar.
Keywords: Keywords: electric aviation, electric propulsion system, battery technology, propeller optimization, simulation